Kecemasan pada korban catcalling: Bagaimana peranan emotion focused coping? - Zulkarnaen, Eylen Bilqish; Aliffia Ananta; I Gusti Ayu Agung Noviekayati (INNER: Journal of Psychological Research, 2023)
Abstract This study aims to determine the relationship between Emotion-Focused Coping and Anxiety in Victims of Catcalling. This research uses quantitative research methods. The sampling technique used was a purposive sampling technique with 115 female respondents aged 18-25 years as the sample. Retrieval of data using Google form. In this study using the scale of emotion-focused coping and anxiety. The instrument in this study uses a Likert scale. Each variable is calculated using the Statistical Product and service solution version 25.0 for Windows using the Spearman-Brown correlation method. This research shows significant results, thus supporting the assumption that the higher the emotion-focused coping, the higher the anxiety experienced by a victim who experiences catcalling behavior. Keywords: Emotion Focused Coping, Anxiety, Victims of Catcalling